2010
DOI: 10.1002/smi.1350
|View full text |Cite
|
Sign up to set email alerts
|

On the stress by photoperiod, temperature and noise as possible causes of genomic damaging in an animal model

Abstract: Stress is a defense mechanism of an organism and is directly related to homeostasis, which is the equilibrium state of the multitude of organism systems, both among each other and with the environment. Given that stress is a major cause of cellular instability, it is directly related to its loss homeostasis. The present study assessed the changes caused by stress on the genetic material of Rattus norvegicus using micronuclei analysis. A total of 10 males were studied by being submitted to continuous stress fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…It should be noted that bathing is allowed in the pool where the fish were collected, thus there is a greater level of interaction between humans and animals which can cause stress to the resident animals. Adam et al ( 2011 ) demonstrated the direct relationship between stress and the frequency of MNs in cells of Rattus novergicus during changes in circadian cycle, temperature, and noise. Thus, in addition to human presence, these other parameters may have contributed to the stress of the animals and consequently, resulting in an increase in the expression of genomic damage.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that bathing is allowed in the pool where the fish were collected, thus there is a greater level of interaction between humans and animals which can cause stress to the resident animals. Adam et al ( 2011 ) demonstrated the direct relationship between stress and the frequency of MNs in cells of Rattus novergicus during changes in circadian cycle, temperature, and noise. Thus, in addition to human presence, these other parameters may have contributed to the stress of the animals and consequently, resulting in an increase in the expression of genomic damage.…”
Section: Discussionmentioning
confidence: 99%
“…CRIS was able to reduce significant body weight gain from 1 week after onset of restraint in rats [ 53 ]. CRIS promotes immune suppression, inducing lymphocyte reduction [ 35 , 54 ], and exposure of rats to continuous stress from photoperiod, temperature and noise was observed to cause an increase in micronuclei incidence in peripheral RBCs [ 55 ]. A recent study showed that CRIS increased the susceptibility of Trp53 -heterozygous mice to radiation (4 Gy) carcinogenesis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In laboratory animal models, studies showed that CRIPS could significantly reduce body weight gain from 1 week after the onset of restraint in rats [ 51 ] and from the day following onset in mice [ 27 ], and promote immune suppression, inducing lymphocyte reduction [ 27 , 52 , 53 ]. In rats exposed to continuous stress from photoperiod, temperature and noise, a significantly increased incidence of micronuclei in peripheral red blood cells (RBCs) was observed [ 54 ]. In mice, it was demonstrated that PS could reduce the RBCs [ 27 ], alter the responsiveness to carcinogens, accelerate tumor onset, promote tumor progression and growth, and alter tumor type and location [ 55 58 ].…”
Section: Health Consequences Of Ps In Humans and In Animal Modelsmentioning
confidence: 99%